2021
DOI: 10.1093/hmg/ddab168
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated pyruvate kinase activity is crucial for metabolic adaptation and cell survival during mitochondrial dysfunction

Abstract: Deoxyguanosine kinase (DGUOK) deficiency causes mtDNA depletion and mitochondrial dysfunction. We reported long survival of DGUOK knockout (Dguok−/−) mice despite low (<5%) mtDNA content in liver tissue. However, the molecular mechanisms enabling the extended survival remain unknown. Using transcriptomics, proteomics and metabolomics followed by in vitro assays, we aimed to identify the molecular pathways involved in the extended survival of the Dguok−/− mice. At the early stage, the serine synthesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Dguok F180S/F180S mice have not yet been systematically observed for the assessment of their life span. According to our preliminary observation, these animals survived up to 30 weeks without further apparent phenotypical or behavioral abnormalities, in line with the preliminary survival estimates of the murine Dguok KO mouse line (22,25). The differential mitochondrial DNA content in various tissues might play a role in the lean phenotype presented herein, and it seems, that the Dguok F180S/F180S mouse line also possesses su cient compensatory pathways ensuring su cient mitochondrial DNA levels, that do not further in uence their phenotypical appearance and survival.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Dguok F180S/F180S mice have not yet been systematically observed for the assessment of their life span. According to our preliminary observation, these animals survived up to 30 weeks without further apparent phenotypical or behavioral abnormalities, in line with the preliminary survival estimates of the murine Dguok KO mouse line (22,25). The differential mitochondrial DNA content in various tissues might play a role in the lean phenotype presented herein, and it seems, that the Dguok F180S/F180S mouse line also possesses su cient compensatory pathways ensuring su cient mitochondrial DNA levels, that do not further in uence their phenotypical appearance and survival.…”
Section: Discussionsupporting
confidence: 83%
“…The current mouse model has some phenotypic overlap with the previously described Dguok KO model, that is characterized by low body weight and decreased subcutaneous fat layer but also with liver damage (22). Furthermore, this mouse line also presents an altered expression of the enzymes of the Krebs cycle (25). Dguok F180S/F180S mice have not yet been systematically observed for the assessment of their life span.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, fumarate upregulation in the 2-year sample suggests that the citric acid cycle (TCA Cycle), which is cardioprotective, is upregulated 56 (Figure 6B). Similarly, kynurenine, which is neuroprotective but also may play roles in energy production 57 , are upregulated (Figure 6B). The decreased presence of amino acids, such as serine, glutamate, and asparagine, in the aged samples, suggests that faster amino acid metabolism is occurring.…”
Section: Discussionmentioning
confidence: 95%
“…DGUOK provides dAMP and dGMP for mtDNA replication. It has been shown that knockout of Dguok could lead to 95% reduction in mtDNA copy number in livers [ 9 ]. Therefore, our observation indicates liver has higher compensatory capacity to the deficiency in TK2 activity than in DGUOK activity.…”
Section: Discussionmentioning
confidence: 99%